Groundwater geochemistry of shallow and deep aquifers from Jalgaon district, northern Maharashtra (India) - Baride, Mukund; Patil, Sanjaykumar; Golekar, Rushikesh (International Journal of Advanced Geosciences, 2014)
This paper contains assessment of groundwater quality with reference to drinking and agricultural use in Jalgaon district, Northern Maharashtra (India). In present study 53 groundwater samples were collected in post monsoon (2010) and pre monsoon period (2011) from different location of Jalgaon district. Analytical results of geochemical analysis of groundwater compare with World health Organization and Indian Drinking Water Standards. Groundwater quality of study area has been deteriorated predominantly due to over exploration and anthropogenic activities. Geochemistry of groundwater shows that the Ca > Mg > Na > K and HCO3 > Cl > SO4 > CO32- trend. Most of the groundwater samples are observed as Ca-HCO3 Type. Groundwater samples of the study area show higher concentration of TDS (>1000 ppm), Cl (>1000 ppm), NO3 (>45 ppm), K (> 10 ppm), Ca (>200 ppm), HCO3 (> 600 ppm) and B (<1 ppm). Irrigation water quality has been inadequately affected by salinity hazards and residual soluble carbonate (RSC). Keywords: Groundwater Geochemistry, Shallow and Deep Aquifers, Medical Geology, Irrigation Hazards, Deccan Trap, India.